Intrinsic Endobronchial Obstructions in Children from Turkey: Evaluation of 2,555 Flexible Bronchoscopic Procedures - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (KARGER, 2013)
Background: Endobronchial obstructions are rarely seen in children and are often misdiagnosed resulting in delay of definitive treatment. A variety of diseases can cause endobronchial obstructions in childhood, but data is limited as to the frequency, distribution and clinical characteristics of endobronchial obstructions diagnosed with flexible bronchoscopy (FB). Objective: To document endobronchial obstructions detected by FB. Methods: FB results from three pediatric pulmonology centers in Istanbul were evaluated. Results: A total of 2,555 children underwent an FB procedure during the study period. Endobronchial obstructions were detected in 10% (n = 256) of the patients. Among FB in patients who had endobronchial obstructions, the four most common indications for bronchoscopy were persistent infiltrations (30%, n = 72), persistent wheezing (28%, n = 70), chronic cough (26%, n = 66) and atelectasis (23%, n = 59). The most common endobronchial obstructions detected in the patients were aspirated foreign bodies (35.9%, n = 92), endobronchial tuberculosis (31.6%, n = 81), mucous plugs occluding airway (16.7%, n = 43) and granulation scars (6%, n = 16). Other pathologies included hydatid cysts (n = 5), hemangiomas (n = 5), tumors (n = 5), submucosal nodules (n = 5) and polyps (n = 4). Endobronchial obstructions were most commonly located in the right bronchus (51%, n = 130) followed by the left bronchus (33%, n = 85), bilaterally (8%, n = 21) and trachea (8%, n = 20). Conclusions: Endobronchial obstructions can be caused by a number of different diseases which require various medical or surgical treatments. In the presence of clinical or radiological findings suggesting an endobronchial obstruction, FB should be performed promptly. Copyright (C) 2012 S. Karger AG, Basel
Keywords: Endobronchial lesions; Bronchial obstructions; Child; Flexible bronchoscopy; Pediatrics; FIBEROPTIC BRONCHOSCOPY; FOREIGN-BODY; DIAGNOSIS; CHILDHOOD; TUBERCULOSIS; ATELECTASIS; AMYLOIDOSIS; EXPERIENCE; DISEASE